POTENSI JUS BUAH PARE (Momordica charantia L.) SEBAGAI PENGHAMBAT HEMOGLOBIN TERGLIKASI IN VITRO - Widyanto, Muhammad Topan; Suhartono, Eko; Biworo, Agung (Pendidikan Dokter Universitas Lambung Mangkurat, 2015)
Bitter gourdÂ (Momordica charantia) is a fruit that is potentially has the ability to inhibit glycated hemoglobin thus can reduce blood sugar level. The aim of this study is to test the potency of bitter gourd juice as a glycated hemoglobin inhibitor. This is a quasi experimental study with non randomized posttest-only with control group design method, using a reaction model of diabetes consisted of two groups; bitter gourd juice as the test group and gliclazide as the standard group, divided into 10%, 20%, and 30% concentration. IC50 value is used to determine the potency as a glycated hemoglobin inhibitor. The result of this study shows that the value of r = 0,990 with an IC50 value of 69,239%, whereas for glikazid 17,268%. The positive value of r indicates a positive relation between concentration and its potency as a glycated hemoglobin inhibitor. The result thus indicates that bitter gourd juice has a potency as a glycated hemoglobin inhibitorÂ Keywords: glycated hemoglobin, bitter gourd (Momordica charantia), gliclazide